Effect of Fe Doping on Zeolite Bead Nanoparticles for Enhanced Photocatalytic Removal of Phenol - Diyana Faziha Mohamad; Norzahir Sapawe; Amin Safwan Alikasturi; Dayang Norafizan Awang Chee; Siti Kamilah Che Soh; Cecilia Devi Wilfred, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study focused on developing innovative bead catalysts of Fe doping with zeolite nanoparticles utilizing photocatalysis technology to address challenges posed by phenolic compounds. The photocatalytic efficiency of the magnetic zeolite bead catalyst for phenol degradation was evaluated under luminescent conditions. A comprehensive analysis was conducted to examine the influence of pH, catalyst dosage, and initial phenol concentration on degradation performance. The results suggest that these magnetic bead catalysts are highly effective in photodegrading phenol and can be efficiently recovered and reused multiple times during treatment at pH 5, 40 g L-1 of bead dosage and 20 mg L-1 of initial concentration of phenol. The application of magnetic zeolite bead catalysts for wastewater recovery proved to be fast, cost-effective, sustainable, and environmentally friendly. In conclusion, the development of magnetic zeolite bead catalysts presents a promising new solution for wastewater treatment challenges.